Supply chain management strategy, planning, and operation - Chopra, Sunil; Meindl, Peter 1970- (Pearson, 2013)
"For undergraduate and graduate supply chain management courses. Illustrating the key drivers in effective supply chain management. Supply Chain Management illustrates the key drivers of good supply chain management in order to help students understand what creates a competitive advantage. This text also provides strong coverage of analytic skills so students can gauge the effectiveness of the techniques described in the text"--Provided by publisher.